Mechanisms of ginsenosides exert neuroprotective effects on spinal cord injury: A promising traditional Chinese medicine - Qi, Le; Zhang, Jun; Wang, Jinghong; An, Junyan; Xue, Wu; Liu, Qinyi; Zhang, Yan (Frontiers in Neuroscience, 2022)
Spinal cord injury (SCI) is a devastating disorder of the central nervous system (CNS). It is mainly caused by trauma and reduces the quality of life of the affected individual. Ginsenosides are safe and effective traditional Chinese medicines (TCMs), and their efficacy against SCI is being increasingly researched in many countries, especially in China and Korea. This systematic review evaluated the neuroprotective effects of ginsenosides in SCI and elucidated their properties. Methods: All experimental information and summaries used in this review were acquired from peer-reviewed articles in the relevant fields. The PubMed, Web of Science, Google Scholar, and China National Knowledge Infrastructure databases were searched for relevant articles. Information on the manual classification and selection of ginsenosides that protect against SCI is included in this review. Results: A literature survey yielded studies reporting several properties of ginsenosides, including anti-inflammation, anti-apoptosis, anti-oxidative stress, and inhibition of glial scar formation. Conclusions: In this review, we discuss the mechanisms of action of different ginsenosides that exert neuroprotective effects in SCI. These results suggest that after further verification in the future, ginsenosides may be used as adjunctive therapy to promote neurological recovery.